Impact of the Extended Digital Eco-Dynamic on Innovation Performance: An Empirical Study on Small E-Businesses in Indonesia - Yuniarty, Yuniarty; So, Idris Gautama; Abdinagoro, Sri Bramantoro; Hamsal, Mohammad (Frontiers in Psychology, 2022)
This study will answer the factors that influence the innovation performance of small e-businesses in Indonesia during the COVID-19 pandemic. The results of this study are expected to contribute to the development of innovation theory by enriching knowledge in the field of management science in general, especially entrepreneurship theory, especially those related to innovation performance, IT ambidexterity, dynamic capability, environmental uncertainty, and Resource-Induced Coping Heuristic (RICH). This study proposes novelty by examining the effect of acquiring, developing, and protecting resources as dimensions of RICH on innovation performance in turbulent conditions due to the COVID-19 pandemic. This theoretical aspect forms the basis for further research that will develop into a broader scope related to innovation performance in entrepreneurship in Indonesia. This fundamental research uses a questionnaire as a data collection tool tested for validity and reliability before being tested empirically using structural equation modeling partial least squares. Research shows that among the dimensions of RICH, protecting resources is the most influential on innovation performance, followed by acquiring resources and developing resources. Dynamic capability positively affects innovation performance. Environmental uncertainty positively affects dynamic capability. Environmental uncertainty positively affects innovation performance. IT capability positively affects dynamic capability. IT capability positively affects innovation performance. The development of small e-businesses needs to get significant attention. Small e-businesses need to develop mutually beneficial business partnerships and improve the quality of their human resources.